A Putative Serine Protease is Required to Initiate the RIPK3-MLKL—Mediated Necroptotic Death Pathway in Neutrophils - Wang, Xiaoliang; Avsec, Damjan; Obreza, Aleš; Yousefi, Shida; Mlinarič-Raščan, Irena; Simon, Hans-Uwe (Frontiers in Pharmacology, 2021)
Adhesion receptors, such as CD44, have been shown to activate receptor interacting protein kinase-3 (RIPK3) - mixed lineage kinase-like (MLKL) signaling, leading to a non-apoptotic cell death in human granulocyte/macrophage colony-stimulating factor (GM-CSF) – primed neutrophils. The signaling events of this necroptotic pathway, however, remain to be investigated. In the present study, we report the design, synthesis, and characterization of a series of novel serine protease inhibitors. Two of these inhibitors, compounds 1 and 3, were able to block CD44-triggered necroptosis in GM-CSF-primed neutrophils. Both inhibitors prevented the activation of MLKL, p38 mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3’ - kinase (PI3K), hence blocking the increased levels of reactive oxygen species (ROS) required for cell death. Although compounds 1 and 3 partially inhibited isolated human neutrophil elastase (HNE) activity, we obtained no pharmacological evidence that HNE is involved in the initiation of this death pathway within a cellular context. Interestingly, neither serine protease inhibitor had any effect on FAS receptor-mediated apoptosis. Taken together, these results suggest that a serine protease is involved in non-apoptotic CD44-triggered RIPK3-MLKL-dependent neutrophil cell death, but not FAS receptor-mediated caspase-dependent apoptosis. Thus, a pharmacological block on serine proteases might be beneficial for preventing exacerbation of disease in neutrophilic inflammatory responses.